2023
DOI: 10.1021/acssuschemeng.2c05936
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Engineering of an Escherichia coli-Based Biotransformation System to Exclusively Produce Glycolic Acid from Formaldehyde

Abstract: A whole-cell biocatalysis was investigated for the selective synthesis of the industrially relevant C2 chemicals (e.g., glycolic acid (3)) from formaldehyde (1). Escherichia coli cells were engineered to overexpress a carboligase and an aldehyde dehydrogenase from E. coli K-12. Moreover, the side reactions, which dissipate formaldehyde and glycolic acid, were removed to produce glycolic acid to a high conversion. Host cell engineering to apply relatively chemical tolerant E. coli strains as well as substrate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Remarkable consistency in yield from substantially different modes of fermentation and scales could attribute to the orthogonality of FORCE pathways from the host metabolism, which could indicate that further scale up to a higher scale in a bioreactor could be possible without the need for extensive process optimizations. To the best of our knowledge, the titer, rate, and yield of C1 to GA bioconversion reported in this study are the highest reported, exceeding the best result in the literature by more than 2.5-fold and 4-fold in titer and flux, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Remarkable consistency in yield from substantially different modes of fermentation and scales could attribute to the orthogonality of FORCE pathways from the host metabolism, which could indicate that further scale up to a higher scale in a bioreactor could be possible without the need for extensive process optimizations. To the best of our knowledge, the titer, rate, and yield of C1 to GA bioconversion reported in this study are the highest reported, exceeding the best result in the literature by more than 2.5-fold and 4-fold in titer and flux, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The best HACS variants identified from this study exhibit up to a 7.4-fold improvement in catalytic efficiency ( k cat / K M ) toward formaldehyde and a 7.5-fold improvement toward formyl-CoA as substrates compared to the starting reference enzyme, RuHACS (Table ). These are the best kinetic parameters reported for enzymes that catalyze C1–C1 condensation utilizing formaldehyde as the substrate, with orders of magnitude higher compared to engineered FLS and related variants ,, and fold improvements from previously reported native or engineered HACSs , (Figure ). We were able to demonstrate that the superior kinetic parameters from in vitro enzyme characterization translates well into the in vivo bioconversion system as represented by the substantially improved pathway flux and selectivity compared to other studies on formaldehyde-to-GA bioconversion. ,, However, it is also important to note that among high performing HACS variants identified from this study, k cat / K M values do not necessarily represent the specific activity of the enzyme under the conditions tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations